AVERAGE TOTAL HEMISPHERIC EMISSIVITY MEASUREMENT IN THE LWIR SPECTRUM FOR ADHESIVE TAPES USED IN THE THERMOGRAPHY TAPE TEST - Mendes, R. P.; Pottie, D. L. F.; Oliveira, M.; Martins, L. V. S.; Ferreira, R. A. M. (Revista de Engenharia Térmica, 2021)
Thermographers often use comparative methods to estimate surface emissivity. Among the most used is the tape method. In this method a known emissivity tape in the LWIR (Long Wavelength Infrared) spectrum is placed on the surface to be inspected. After thermal equilibrium, the temperature of the tape and the surface under inspection must be the same. In this case, the temperature observed on the tape is the reference temperature. The emissivity of the surface must then be changed until the reference temperature is reached. It is common practice to admit the value of the emissivity of the adhesive tape as 0.95, there are few studies that present these data with metrological rigor, which leads to doubts about the emissivity of the commercial tapes. In this work, experiments were performed on Tekbond, Double A, 3M 101, Rapix, Altape, adhesive tapes for temperatures of 50, 55, 60, 65 and 70ºC. An experimental apparatus was developed through which it was possible to estimate surface reflection, transmission and atmospheric emission for one and two layers of tapes, in order to make emissivity measurements possible. Through the data it was possible to statistically estimate the LWIR average total hemispheric emissivity as well as the acceptance range to 95% certainty, being therefore equal to ε=0.94±0.03. It is possible to arm, therefore, that the value of 0.95, usually used as emissivity of the adhesive tape, is extremely reasonable because it is 0.01 of the average value of the Gaussian distribution calculated by this work.